A bio-energetic model of cyclist for enhancing pedelec systems. Issue 1 (July 2017) - Rosero, Nadia; Martinez, John J.; Leon, Henry
Abstract: The paper presents a whole-body bio-energetic model of a cyclist which includes the mechanical dynamics of the bike. This model could be used to solve control-design problems for pedelec systems. The behavior of some physiological variables during cycling is reproduced by keeping an energy aware transfer flow. The modeling approach considers three main levels: i) physiological, ii) bio-mechanical and iii) pure-mechanical. Physical laws of energy/mass conservation were applied to simulate the ways in which energy is stored, transferred and dissipated at each level. A simulation example shows a scenario of a physiological test.